EFFECT OF COMMERCIAL RATION REPALCEMENT WUTH BREAD WASTE ON THE PERFORMANCE OF SUPERIOR KAMPUNG CHICKEN BALITNAK (KUB) - M. A., Ardiyansyah; Wibawa, A. A. P. P.; Siti, N.W. (Jurnal Peternakan Tropika; Vol 11 No 3 (2023): Vol. 11 No. 3 Tahun 2023; September - December, 2023)
This study aims to determine the effect of replacing commercial rations with bread waste on the performance of superior kampung chicken balitnak (KUB). his research was conducted at a farm located on Jalan Banjar Tengah Gulingan, Gulingan Village, Mengwi District, Badung Regency, for 8 weeks. The design used was a completely randomized design (CRD) consisting of 3 treatments and 5 replications so that there were 15 experimental units. Each experimental unit was filled with 2 KUB chickens with homogeneous weight. The three treatments were KUB chickens fed a commercial ration without bread waste (P0), KUB chickens being given 75% commercial ration + 25% bread waste (P1) and KUB chickens being given 50% commercial ration + 50% bread waste (P2). The variables observed were initial body weight, final body weight, weight gain, ration consumption, water consumption and Feed Conversion Ratio (FCR). The final body weight of KUB chickens treated with P0, P1 and P2 statistically showed significantly different results (P<0.05). The weight gain that received P1 and P2 treatments was statistically significantly (P<0.05) lower than P0 treatment. The Feed Conversion Ratio (FCR) which received P1 and P2 treatments was statistically significantly (P<0.05) higher than P0 treatment. From the results of the study, it can be concluded that KUB chickens given 75% commercial ration + 25% bread waste (P1) and KUB chickens given 50% commercial ration + 50% bread waste (P2) reduced the appearance of KUB chickens. Lose final weight, decrease body weight gain and increase the value of Feed Conversion Ratio (FCR). Keyword: KUB Chicken, Performance, Bread Waste .